Comparative investigation on feasible hydrolysis H2 production behavior of commercial Mg‐M (M = Ni, Ce, and La) binary alloys modified by high‐energy ball milling—Feasible modification strategy for Mg‐based hydrogen producing alloys. (27th August 2020) - Hou, Xiaojiang; Shi, Hongchang; Yang, Lu; Feng, Lei; Suo, Guoquan; Ye, Xiaohui; Zhang, Li; Yang, Yanling
Summary: The bulk Mg‐M (M = Nickel [Ni], cerium [Ce], and Lanthanum [La]) alloys are successfully ameliorated by high‐energy ball milling (HEBM) to modify the hydrolysis H2 generation performance in simulated seawater solution (3.5 wt% NaCl). The H2 generation kinetics, rate‐limiting steps, thermodynamics and the hydrolysis mechanism are investigated by combining the fitting results of the hydrolysis curves and microstructures information. The results indicate that the as‐cast Mg25Ni possesses higher generation capacity and faster initial rate. The capacities of as‐cast Mg25Ni, Mg30Ce, and Mg30La alloys at 48°C within 180 minutes are 760 mL g −1, 725 mL g −1, and 525 mL g −1 . The hydrolysis H2 generation apparent activation energies of the as‐cast Mg25Ni, Mg30Ce, and Mg30La alloys are 30.92, 17.05, and 28.04 kJ·mol −1, respectively. The HEBM technique can elevate the hydrolysis performance of Mg‐M alloys. And the highest H2 producing capacity as high as 589 mL g −1 is obtained by HEBM Mg30La alloy at 48°C within 30 minutes. The hydrolysis apparent activation energies E a are 9.57, 14.65, and 23.88 kJ/mol for HEBM Mg25Ni, Mg30Ce, and Mg30La alloys. The initial rate and the final yield of H2 generation for Mg‐based alloys are affected by the activity of matrix alloy, microstructure, particle size, surface state, and many other factors. Abstract : The capacities of as‐cast Mg25Ni at 48°C in NaCl solution are as high as 760 mL g −1 . HEBM can elevate the generation rate, capacity and yield within short period. The hydrogen generation performance mainly dominated by the coordinated factors.